A Visual Lexicon - Cohn, Neil (Public Journal of Semiotics, 2007)
One of the most recognizable graphic components of the visual language of “comics” is the “panel,” a demarcated frame of image content put into discrete sequences, thereby seeming to be the primary unit of expression. However, meaningful visual elements do exist that are both smaller and larger than this encapsulation of image and text. Spoken languages also have variation in sizes of lexical items above and below their primary sequential unit of the “word.” This paper will address these varying levels of representation in visual language in comparison to the structural make-up of verbal language, to aim toward at what it means to have “visual lexical items.”